Początki politycznej kariery czołowych polityczek CDU i CSU na poziomie federalnym w Niemczech w latach 1991–2018 - Piotrowska, Marlena (Rocznik Polsko-Niemiecki, 2020)
The article focuses on the first steps in the political career of female politicians from the Christian Democratic Union (CDU) and the Christian Social Union (CSU), who assumed top political positions at the federal level in Germany between 1991 and 2018. The author analyses when the female leaders of the CDU and CSU took their first parliamentary seats in the German Bundestag, when they obtained the first leading positions at the federal level, and also how many years after joining the party this took place. It is also interesting whether top female politicians took their first parliamentary seats through votes in direct districts or thanks to the party list (second votes). Do the career paths of the female politicians from the Christian Democrats fit the model of typical career paths, or do they also include those who have avoided key positions on their way to the top?